Interorganellar signaling in age-related disease - Mattson, Mark Paul (Advances in cell aging and gerontology, 2001)
Collectively, the chapters in this work will provide the reader with novel insight into the inter-relationships of the function of different organelles in the sequences of events that lead to cellular dysfunction and degeneration in the aging human population. The chapters are rich in information for cell and molecular biologists pursuing studies of the different diseases covered. In addition, the clinician will find value in understanding mechanisms underlying age-related disease as such an understanding will lead to novel therapeutic approaches for an array of age-related diseases.